Credibility of Chromomycin A3 Staining in Prediction of Fertility - Mohammad Hossein Nasr-Esfahani; Roshanak Aboutorabi; Shahnaz Razavi (International Journal of Fertility and Sterility, 2009)
Background Chromomycin A3 (CMA3) staining has been used to assess protamine deficiency. The aim of this study was to determine credibility of CMA3 along with semen parameters for assessment of fertility potential.